E-TECHNOLOGY FOR MONITORING MEDICAL STUDENT’S ACADEMIC PERFORMANCE IN QUALITY MANAGEMENT SYSTEM OF EDUCATION - Ksenia A. Mitrofanova; Petr V. Ivachev; Konstantin V. Kuzmin (Высшее образование в России)
This paper presents the experience of applying e-Technology to monitor student’s academic performance and as a means to enhance student’s motivation. The advantages of using e-Learning and interactive methods are described. We used educational e-content options to make the results of students’ academic performance available on-line both for students and teachers. This opportunity was enthusiastically accepted by all participants of the educational process. Moreover, this approach was relevant to the level of students’ information culture. The majority of students continued to use the Internet for educational purposes more actively. Furthermore, some students developed their skills in using e-Learning technologies.